2007
DOI: 10.1186/1471-2164-8-229
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic hybridizations reveal absence of large Streptomyces coelicolor genomic islands in Streptomyces lividans

Abstract: Background: The genomes of Streptomyces coelicolor and Streptomyces lividans bear a considerable degree of synteny. While S. coelicolor is the model streptomycete for studying antibiotic synthesis and differentiation, S. lividans is almost exclusively considered as the preferred host, among actinomycetes, for cloning and expression of exogenous DNA. We used whole genome microarrays as a comparative genomics tool for identifying the subtle differences between these two chromosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
66
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 60 publications
(65 reference statements)
6
66
1
Order By: Relevance
“…Interestingly, AICESco5349 flanks the whiE cluster (Bentley et al, 2002) encoding the enzymes to synthesise the grey polyketide spore pigment (Davis and Chater, 1990) and AICESco3250 flanks the calcium-dependent antibiotic (CDA) biosynthetic gene cluster. The two AICEs are absent on the highly syntenic core region of the S. lividans genome (Jayapal et al, 2007) and the S. ambofaciens genome lacks the CDA cluster and also the complete region containing the whiE cluster and AICESco5349 (Choulet et al, 2006). Possibly, these AICEs are associated with the acquisition of these secondary metabolite clusters in S. coelicolor.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, AICESco5349 flanks the whiE cluster (Bentley et al, 2002) encoding the enzymes to synthesise the grey polyketide spore pigment (Davis and Chater, 1990) and AICESco3250 flanks the calcium-dependent antibiotic (CDA) biosynthetic gene cluster. The two AICEs are absent on the highly syntenic core region of the S. lividans genome (Jayapal et al, 2007) and the S. ambofaciens genome lacks the CDA cluster and also the complete region containing the whiE cluster and AICESco5349 (Choulet et al, 2006). Possibly, these AICEs are associated with the acquisition of these secondary metabolite clusters in S. coelicolor.…”
Section: Discussionmentioning
confidence: 99%
“…These observations demonstrate that the regulatory circuits controlling the morphological differentiation process are somehow different in these two closely related species. Despite the overexpression of SCO3201, S. lividans sporulates, indicating either that some of the SCO3201 operator sites are missing in front of key genes involved in the positive regulation Indeed, it was demonstrated that some genomic islands larger than 25 kb and comprising more than 600 genes were present in the S. coelicolor genome but absent in the S. lividans genome (30). The SCO3201 regulator was shown to negatively autoregulate its own synthesis, and its operator site in its own promoter region was identified as the 15-bp palindromic sequence (TG GCAGATTCTGCCA) that is a typical binding site for homodimer transcriptional regulators of the TetR family (51).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of gene divergence or absence has already been thoroughly investigated in many closely related organisms (21,24,29,41,43). Often, loss or alteration of genetic content is affected by the activity of IS elements (7,28).…”
Section: Discussionmentioning
confidence: 99%
“…paratuberculosis (49) and Tropheryma whipplei strains (27). In addition, the absence of five Streptomyces coelicolor genomic islands were reported in Streptomyces lividans (24), and differences in gene content were detected in other species, Salmonella enterica (38) and Xylella fastidiosa (26). In this work we compared the genomes of nine strains of L. helveticus which were isolated from the dairy environment.…”
mentioning
confidence: 99%